2010
DOI: 10.1177/1359104510365041
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing adoptive parenting: A randomized controlled trial

Abstract: The aim was to conduct a pragmatic randomized controlled trial (RCT) to evaluate two parenting programmes designed for adopters of children late placed from care. Adoptive parents, with children between 3 and 8 years who were screened to have serious behavioural problems early in the placement, participated in home-based, manualized, parenting programmes delivered by trained and supervised family social workers. The adopters who agreed to join the study were randomly allocated to one of two parenting intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 17 publications
0
74
0
Order By: Relevance
“…Six papers [619][620][621]623,626,628 were excluded because they did not involve an intervention and four papers 587,618,624,625 because the intervention in question did not meet criteria for inclusion, focusing on prevention rather than treatment. Two records 622,627 did not have a specific focus on maltreatment, three records 116,504,588 did not meet criteria for a full economic evaluation and one record 617 was a conference abstract.…”
Section: Excluded Economic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Six papers [619][620][621]623,626,628 were excluded because they did not involve an intervention and four papers 587,618,624,625 because the intervention in question did not meet criteria for inclusion, focusing on prevention rather than treatment. Two records 622,627 did not have a specific focus on maltreatment, three records 116,504,588 did not meet criteria for a full economic evaluation and one record 617 was a conference abstract.…”
Section: Excluded Economic Studiesmentioning
confidence: 99%
“…A total of 16 papers 116,504,587,588,[617][618][619][620][621][622][623][624][625][626][627][628] were excluded from the review of economic evidence and these are reported in Table 10. Six papers [619][620][621]623,626,628 were excluded because they did not involve an intervention and four papers 587,618,624,625 because the intervention in question did not meet criteria for inclusion, focusing on prevention rather than treatment.…”
Section: Excluded Economic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been challenging for adoptive parents to access appropriate support (Rushton, Monck, Leese, McCrone, & Sharac, 2010) and it has been unclear which are likely to be the best models for intervention as children's problems can seem entrenched. A recent randomised controlled trial comparing two models of parenting intervention for adoptive families suggested that adoptive parents "had greater capacity to change than the children" (Rushton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%